Los social media en la educación digital del estudiante universitario - Martínez Bonilla, Carlos (2017)
The Internet development social media have become a communication form, innovative inclusion proposals in the education process of the students in the institutions of higher education (IES) to be important. The proper use of virtual platforms, digital tools online, allows work in the different virtual learning modalities, which have established parameters at work in social networking, educational platforms, pages on the internet among others, the management of these activities have allowed to determine characteristics to take into account such as organization, planning, connectivity and interactivity in virtual work without neglecting the development of the activities in the classroom. Manage relationships online, presentations and publications in the Web 2.0 tools, based on the technological revolution worldwide has given way to an informational society, defined the generation, management and use of data in the digital environment. The IES have treated of include as a complement in the education face-to-face, generating environments interactive through the connectivity. Through research - action, it seeks to integrate the reflection and intellectual work through experiences of proper use of the tools in the classroom online. Is analyzed data through an approach quantitative and qualitative using instruments and techniques of collection of information, data taken in the Law Faculty an Social Science of